Biosynthesis of zinc oxide nanoparticles using the supernatant of Weissella cibaria UPM22MT06 and its antibacterial and cytotoxicity properties - Al-Tameemi, Ahmed Issa; Masarudin, Mas Jaffri; Abdul Rahim, Raha; Mills, Toby; Timms, Verlaine J; Neilan, Brett A; Mat Isa, Nurulfiza (Springer, 2023)
Developing eco-friendly methods for synthesizing nanoparticles is a significant step in nanotechnology and will allow increased applications in nanomedicine. Wastewater contains bacteria with high tolerance to toxic substances and enzymatic reduction ability and has the potential to be rich in species that can synthesize nanoparticles. This research aimed to isolate suitable bacterial candidates, generate zinc oxide nanoparticles (ZnO NPs), and assess their effectiveness in inhibiting methicillin-resistant Staphylococcus aureus (MRSA). Two Weisella cibaria (W. cibaria) strains (UPM22MT02 and UPM22MT06) were isolated from a wastewater treatment plant in Johor, Malaysia, and screened for ZnO NPs synthesis. Weissella are Gram-positive lactic acid bacteria belonging to the Leuconostocaceae family. ZnO NPs were synthesized successfully using the supernatant of both strains. The bacterial strain, W. cibaria UPM22MT06, produced the highest concentration of ZnO NPs by weight and as a result was selected for further characterization. Biosynthesized ZnO NPs were identified using UV-visible spectroscopy, Fourier-transform infrared spectroscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, and dynamic light scattering. Monodisperse spherical ZnO NPs of 2.3–7.5 nm were obtained with 0.1 M zinc nitrate at 80 °C. Vigorous inhibitory activity of biosynthesized ZnO NPs against MRSA was observed with minimum inhibitory concentrations of 0.625 mg/mL and minimum bactericidal concentrations of 1.25 mg/mL. MTT– (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assays indicated that ZnO NPs showed no toxicity on the fibroblast cell line HS-27. The ZnO NPs synthesized by W. cibaria UPM22MT06 are potent antibacterial agents that are both non-toxic and eco-friendly.